THE EFFECT OF INFESTATION OF TERMITEMicroceritermes diversus (SILVESTRI) (INSECTA:ISOPTERA)ON THE PRODUCTIVITY OF SOME DATE PALMSCULTIVARS IN IRAQ - Shefik, Maan (Iraqi Journal of Science, 2024)
This study was conducted to evaluate the effect of the termite Microcerotermesdiversus (Silvestri) on the productivity of some date palm cultivars in 5 governoratesof Iraq: Babylon, Waset, Kerbela, Qadesyia and Basrah. It was found that thepercentages of infestation in general for the following cultivars: 32.6% for Hellawy,for Zehdy was 29.5% and then infestation decreased gradually within cultivars andlowest percentage was 6.1% for Berhy, The percentages of infestation forgovernorates level were the highest in Waset for Zehdy was 45.5% and lowest forBerhy, was 6.1% in Basrah. This confirms that Zehdy was more susceptible thanother cultivars for infestation by termite M. diversus, many factors are interferenceto increase the percentage of infestation, like shortage of agricultural practices alsonever performance protection control and controlling when the infestation happenand carelessness to orchard by owners or by renters that affect on average theproduction of date palm tree then on general production of orchard and lead to deathnumerous of date palm trees.